(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. Atherosclerosis is associated with increased intima- media thickness (IMT) and vascular calcification (VC) in maintenance hemodialysis (MHD) patients. Fetuin-A is a serum protein, which inhibits vascular calcification. The aim of this study was to investigate the association between fetuin-A and VC, in a group of MHD patients. Methods. One hundred and forty-three MHD patients were included and followed for 3 years. Blood samples were studied for calcification and inflammation markers and fetuin-A was checked 3 times at the start, middle and the end of the study. We used common carotid doppler sonography for assessment of indices of VC, which were performed at baseline and at the end of the study. Vascular calcification was defined as a common carotid intima media thickness ≥ 0.8 mm on either side or the existence of any plaque or stenosis ≥ 50% on either side. Results. From 143 patients (mean age 57.5 ± 15.9, 60.1% male), 104 patients (75.4%) had VC at baseline. The mean age and the prevalence of DM were significantly higher in patients with VC (P < .001 for both). There was no significant difference in the levels of Pi, PTH, and fetuin-A between the two groups. In a multiple logistic regression model at baseline only age (OR = 1.09, P < .001), and diabetes mellitus (OR = 4.59, P < .05) were associated with VC and dialysis vintage had a marginal association (OR = 1.20, P = .09). At the end of the study only age (OR = 1.12, P < .001), and CRP (OR = 1.14, P < .05) were associated with VC. The mean survival of patients with VC was significantly lower than the patients without VC (31.87 ± 0.95 vs. 33.73 ± 1.29, P < .05), however the mortality was not affected by fetuin-A level. Conclusion. Survival rate of patients without VC was higher than the patients with VC. We didn’t find any correlation between the level of fetuin-A and VC. It seems that the traditional risk factors of VC, including age and diabetes mellitus are the main predictors of VC in MHD patients.